Ancient Jewish-Christian dialogues: Athanasius and Zacchaeus, Simon and Theophilus, Timothy and Aquila ; introductions, texts, and translations - Varner, William; Athanasius Celeta 489/496; Zacchaeus Christianus 420 (Studies in the Bible and early Christianity, 2004)
The dialogue of Athanasius and Zacchaeus -- The dialogue of Simon and Theophilus -- The dialogue of Timothy and Aquila